Population, natural resources and territorialized power: a supratemporal theoretical perspective - Matos, Ralfo (2012)
The present analysis discusses the sociopolitical and territorial relations that cover the demographic dynamics, natural resources and exercising power at different historical moments. The reflections on contemporary China and its economic development as a strong consumer of natural resources is a parameter for establishing connections with other historical periods in which the combination of power, resources and population as a triad has always been present. Four historical periods are underscored: the passage from Pleistocene to Holocene; the flourishing of the Greek civilization; the 16th Century European restructuring; and the industrializing spurt as of the end of the 18th Century, which introduced a long period of European economic hegemony. Structures of political power, population, and of resources of survival and prominence are crucial in order to understand the organization of expansion projects led by European and non-European countries, especially beginning the 19th century, a moment in which rivalries and geopolitical interests became explosive and organized international labor divisions that reproduced themselves extensively. The analyses and examples described allow questioning if the expansionist ideary is not currently taking over new features, even if no longer exclusively territorialist. There is strong evidence that the grandiloquent collective memory rekindles ancient founding myths that value national identities in barely rational environments, in which the perspective of maximizing profits and opportunities is compelling.